DEVELOPMENT OF EMERGING COUNTRIES AND INCIDENCE OF ECONOMIC STRESS FACTORS - SIMIONESCU, Irina; ENESCU, George (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Emerging countries have had a spectacular evolution over the past 10 years and they seem to have crossed the economic crisis better. This results from the analysis of economic indicators. Which, then, was the social and economic stress accumulated for these efforts as concerns emerging countries in comparison with developed countries? Is human resource erosion higher in emerging or in developed countries? This paper aims to identify and analyze stress factors faced by organizations and a population in emerging countries given the tough economic conditions that crossing. The analysis showed that stressors faced by emerging countries are experiencing high costs both economic and especially social and long term these effects can be devastating to populations and economies of these countries.